Nanomarketing: A New Frontier for Neuromarketing. Issue 8 (8th July 2016) - Mileti, Antonio; Guido, Gianluigi; Prete, M. Irene
ABSTRACT: The emergence of neuromarketing has significantly advanced conventional marketing research, illuminating how unconscious responses and emotions impact consumers' perceptions and decision‐making processes. Neuromarketing is founded on the assumption that individual sensory and motor systems can be identified in specific networks of brain cells, the observation of which can reveal the unconscious or emotional characteristics of consumer decision making. Yet, neuromarketing technologies present several limitations that can impede the extension and validation of their application: (i) the development of high‐priced and time‐restricted neuroimaging experiments; (ii) the employment of large and immovable devices confined to artificial laboratory environments; (iii) the use of a single neuroimaging technology at a time (usually the functional magnetic resonance imaging); (iv) the use of a single nonneuroimaging device at a time; and (v) the potentially unethical manipulation of research subjects. One way to address these issues involves nanotechnologies, which present a ground‐breaking opportunity for neuromarketing research. These technologies encompass not only the traditional notion of structures, devices, and systems created by limiting shape and size at the nanometer scale, but also the new miniaturized tools based on one or more nanocomponents. The integration of neuromarketing and nanotechnologies could start a new field of research, which is termed here nanomarketing . Nanomarketing makes it possible to: (i) carry out noninvasive and nonintrusive experiments in shopping places; (ii) monitor consumers' mental processes in real time; (iii) combine different technologies to corroborate results obtained by different neuroscientific tools; (iv) integrate neurophysiological field indicators with laboratory neuroimaging results; and (v) highlight ethical issues raised by the use of these novel, portable, and easy‐to‐use nanodevices. This study thus has a twofold aim: (i) investigating both the limitations and opportunities, for researchers and practitioners, that accompany the miniaturization process and application of nanotechnologies to neuromarketing; and (ii) providing a critical review of the aforementioned limitations, highlighting the theoretical and managerial implications, and summarizing the discussion for future research.